Coal-based hard carbon material as well as preparation method and application thereof

The coal raw materials and soft carbon precursors after crushing and sieving and pickling are carbonized in an inert atmosphere and undergo secondary sintering and curing, the soft carbonization and low efficiency problems of coal-based hard carbon materials during carbonization at high temperatures are solved. High sodium storage capacity and excellent sodium ion battery performance are achieved.

CN119306202APending Publication Date: 2025-01-14ZHUHAI NAYI NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411266642.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing coal-based hard carbon materials are prone to soft carbonization trends during carbonization at high temperatures, small layer spacing, low sodium storage capacity and low first charge and discharge efficiency. The preparation process is complicated, making it difficult to balance capacity and efficiency.

Method used

By crushing and sieving coal raw materials, eluting them with the soft carbon precursor and carbonized under an inert atmosphere, and secondary sintering and curing with the capillary agent, the surface irreversible defects are reduced, the reversible active sites are increased, and the storage is improved Sodium capacity and first charge and discharge efficiency.

Benefits of technology

The prepared coal-based hard carbon material has high specific surface area and excellent electrochemical properties. It has a first charge and discharge efficiency of 90%, and a reversible capacity of up to 317mAh/g. It is suitable for sodium ion battery negative electrode materials, showing high energy density and long cycles. life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005037316180000101
    Figure BDA0005037316180000101
  • Figure BDA0005037316180000111
    Figure BDA0005037316180000111
Patent Text Reader

Abstract

The invention discloses a coal-based hard carbon material as well as a preparation method and application thereof. The method comprises the following specific steps: crushing and screening a coal-based raw material, pickling and deliming to obtain ultra-pure coal powder; mixing the ultra-pure pulverized coal with the soft carbon precursor, and performing carbonization treatment in an inert atmosphere; and mixing the carbonized sample with a solvent, and carrying out secondary sintering and curing to obtain the coal-based hard carbon material. The soft carbon precursor coating layer is used for reducing surface irreversible defects and improving coulombic efficiency and electronic conductivity, oxygen-containing functional groups such as carbonyl are introduced and cured in combination with the capacity increasing agent and secondary sintering, more reversible active sites are provided, and higher disorder degree and more excellent electrochemical performance are obtained. The preparation method is low in raw material cost and simple in treatment process, and is a sodium ion battery negative electrode material with commercialization prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a coal-based hard carbon material and a preparation method and application thereof. Background Art

[0002] At present, the raw materials for preparing hard carbon mainly include biomass, high molecular polymers and asphalt. There are generally problems such as low carbon yield, high raw material cost and complex preparation process, which have imposed certain restrictions on further industrial application and development. Coal, as one of the carbon sources of hard carbon, has the advantages of abundant resources and low cost, and is one of the preferred materials for preparing hard carbon. However, due to the soft carbonization trend of coal during high-temperature carbonization and the small interlayer spacing, the sodium storage capacity is low. At the same time, the gaseous CO2, CO, CH4 and other gases generated during the high-temperature cracking of coal escape to produce mesopores, macropores and defects, resulting in low initial charge and discharge efficiency. Therefore, how to reduce surface irreversible defects, increase surface active sites, and improve sodium storage capacity and initial charge and discharge efficiency are technical problems that need to be solved urgently.

[0003] In recent years, researchers have used a method of secondary improvement of coal-based materials to improve electrochemical performance. CN118062827A discloses a method for preparing a bituminous coal-based hard carbon material that combines pre-pore formation with high-temperature carbonization. The pre-pore formation effect is achieved by ball-milling a mixture of coal-based materials and basic zinc carbonate, and then the sodium storage capacity is increased by removing the template and high-temperature carbonization to close the pores. However, the above scheme fails to comprehensively measure the relationship between capacity and initial effect, and the preparation process is relatively cumbersome. Therefore, how to reduce the irreversible defects on the surface of coal-based hard carbon materials after carbonization, increase reversible active sites, and balance the sodium storage capacity and initial charge and discharge efficiency is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a coal-based hard carbon material, using coal, which is abundant in resources and low in cost, as a hard carbon source.

[0005] Another object of the present invention is to provide a coal-based hard carbon material prepared by the above preparation method, which has higher capacity and first coulombic efficiency.

[0006] Another object of the present invention is to provide application of the above-mentioned coal-based hard carbon material in sodium ion batteries.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a coal-based hard carbon material comprises the following steps:

[0009] (1) crushing, screening, acid washing and deashing the coal raw materials to obtain ultra-pure coal powder;

[0010] (2) mixing the ultrapure coal powder obtained in step (1) with a soft carbon precursor and carbonizing the mixture under an inert atmosphere;

[0011] (3) The carbonized sample obtained in step (2) is mixed with a volume extracting agent and subjected to secondary sintering and curing to obtain a coal-based hard carbon material.

[0012] Preferably, the coal raw material in step (1) is selected from at least one of anthracite, coking coal, fat coal, gas coal, weakly sticky coal and lignite.

[0013] Preferably, the coal raw material in step (1) is crushed and screened into coal powder with a particle size D50 of 4 to 10 μm.

[0014] Preferably, the acid washing and deashing in step (1) refers to adding the crushed coal powder into an acid washing and deashing solution, washing with water until the pH value is 6 to 8, and drying to obtain ultra-pure coal powder with an ash content of ≤0.5wt%.

[0015] Preferably, the soft carbon precursor in step (2) is at least one of petroleum asphalt, coal tar pitch and asphalt mesophase.

[0016] Preferably, the mass ratio of the soft carbon precursor to the ultrapure coal powder in step (2) is (5-30):100; more preferably (10-30):100; most preferably 10:100.

[0017] Preferably, the carbonization temperature in step (2) is 1000-1600° C.; the heating rate is 1-10° C. / min; and the insulation time is 1-10 h.

[0018] More preferably, the carbonization temperature is 1000-1600° C.; the heating rate is 5-10° C. / min; and the insulation time is 2-10 h.

[0019] More preferably, the carbonization temperature is 1300-1400° C.; the heating rate is 5-10° C. / min; and the insulation time is 2-5 h.

[0020] Preferably, the inert atmosphere in step (2) refers to at least one of nitrogen, helium and argon.

[0021] Preferably, the extracting agent in step (3) is at least one of p-formylbenzoic acid, o-carboxyphenylacetic acid and salicylaldehyde.

[0022] Preferably, the mass ratio of the volume extracting agent to the carbonized sample in step (3) is (1-10):100; more preferably (2-10):100; most preferably (2-5):100.

[0023] Preferably, the secondary sintering curing temperature in step (3) is 100-300° C.; the heating rate is 1-10° C. / min; and the heat preservation time is 1-10 h.

[0024] More preferably, the secondary sintering curing temperature is 100-300° C.; the heating rate is 5-10° C. / min; and the heat preservation time is 2-10 h.

[0025] More preferably, the secondary sintering curing temperature is 200° C., the heating rate is 5° C. / min, and the heat preservation time is 2 h.

[0026] Preferably, the secondary sintering and solidification in step (3) is carried out under an inert atmosphere.

[0027] More preferably, the inert atmosphere is at least one of nitrogen, helium and argon.

[0028] The coal-based hard carbon material prepared by the above preparation method.

[0029] The coal-based hard carbon has a specific surface area of ​​2 to 20 m 2 / g, the first charge capacity is 270-320mAh / g, and the first charge and discharge efficiency is ≥85%, showing excellent electrochemical performance.

[0030] The above-mentioned coal-based hard carbon material is used as a negative electrode material for sodium ion batteries.

[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0032] The coal-based hard carbon material provided by the present invention has a simple preparation process and low raw material cost. First, by selecting suitable types of coal, including anthracite, coking coal, fat coal, gas coal, weakly sticky coal, lignite, etc., crushing and screening to a D50 of 4 to 10 μm, and then evenly mixing with soft carbon precursors such as petroleum asphalt, coal tar asphalt, asphalt intermediate phase, and co-carbonizing, a soft carbon layer is coated on the surface, blocking the mesopores and macropores generated by the escape of gases such as CO2, CO, and CH4 cracked from the coal-based raw materials during the carbonization process, reducing surface irreversible defects and improving electronic conductivity, thereby improving the first charge and discharge efficiency. Then, the carbonized material is evenly mixed with the capacity-enhancing agent and then sintered and solidified at low temperature, and oxygen-containing functional groups such as carbonyl are introduced on the surface of the carbonized material to provide reversible active sites for sodium ion adsorption. The above process makes the coal-based hard carbon finally prepared conducive to the transmission and storage of sodium ions. The hard carbon material prepared by this method has a suitable d 002 The interlayer spacing, abundant active sites and higher sodium storage capacity, its reversible capacity is as high as 317mAh / g, and the first charge and discharge efficiency is as high as 90%, showing excellent sodium ion battery performance. The present invention provides coal-based hard carbon materials with high energy density, long cycle life, excellent rate performance and low cost, and has very promising industrial prospects. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0034] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0035] Example 1

[0036] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0037] (1) Crushing the lump anthracite into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0038] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt %;

[0039] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 3 g of petroleum asphalt and placed in a tubular furnace. The mixture was heated to 1300 °C at 5 °C / min under a nitrogen atmosphere, kept at this temperature for 5 h, and cooled to room temperature to obtain a carbonized sample.

[0040] (4) The carbonized sample obtained in step (3) was mixed evenly with o-carboxyphenylacetic acid in a mass ratio of 100:2 and placed in a tubular furnace. The mixture was heated to 200°C at a rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0041] Example 2

[0042] The difference between this embodiment and embodiment 1 is that the mass ratio of petroleum asphalt to coal powder in step (3) is 30:100. The remaining steps and parameters are the same as those in embodiment 1.

[0043] Example 3

[0044] The difference between this embodiment and embodiment 1 is that the mass ratio of petroleum asphalt to coal powder in step (3) is 5:100. The remaining steps and parameters are the same as those in embodiment 1.

[0045] Example 4

[0046] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0047] (1) crushing the lump fat coal into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0048] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt%;

[0049] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 3 g of petroleum asphalt and placed in a tubular furnace. The mixture was heated to 1600° C. at a rate of 10° C. / min under a nitrogen atmosphere, kept at this temperature for 10 h, and cooled to room temperature to obtain a carbonized sample.

[0050] (4) The carbonized sample obtained in step (3) was mixed evenly with o-carboxyphenylacetic acid in a mass ratio of 100:2 and placed in a tubular furnace. The temperature was raised to 300°C at 5°C / min under a nitrogen atmosphere, kept at this temperature for 10 h, and cooled to room temperature to obtain a hard carbon material.

[0051] Example 5

[0052] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0053] (1) crushing the lump gas coal into coal powder, filtering the sieve through a 325-mesh sieve, and controlling the coal powder particle size D50 to be 4 to 10 μm;

[0054] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt%;

[0055] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 3 g of petroleum asphalt and placed in a tubular furnace. The mixture was heated to 1000° C. at 5° C. / min under a nitrogen atmosphere, kept at this temperature for 10 h, and cooled to room temperature to obtain a carbonized sample.

[0056] (4) The carbonized sample obtained in step (3) was mixed evenly with o-carboxyphenylacetic acid in a mass ratio of 100:10 and placed in a tubular furnace. The mixture was heated to 200°C at a rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0057] Example 6

[0058] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0059] (1) crushing the lump gas coal into coal powder, filtering the sieve with a 325-mesh sieve, and controlling the coal powder particle size D50 to be 4 to 10 μm;

[0060] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt %;

[0061] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 3 g of petroleum asphalt and placed in a tubular furnace. The mixture was heated to 1000° C. at 5° C. / min under a nitrogen atmosphere, kept at this temperature for 10 h, and cooled to room temperature to obtain a carbonized sample.

[0062] (4) The carbonized sample obtained in step (3) was mixed evenly with o-carboxyphenylacetic acid in a mass ratio of 100:2 and placed in a tubular furnace. The mixture was heated to 200°C at a rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0063] Example 7

[0064] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0065] (1) Crushing lump coking coal into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0066] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt %;

[0067] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 6 g of coal tar pitch and placed in a tubular furnace. The mixture was heated to 1600° C. at a rate of 10° C. / min under a nitrogen atmosphere, kept at this temperature for 10 h, and cooled to room temperature to obtain a carbonized sample.

[0068] (4) The carbonized sample obtained in step (3) was mixed evenly with o-carboxyphenylacetic acid in a mass ratio of 100:2 and placed in a tubular furnace. The mixture was heated to 100°C at a rate of 5°C / min under a nitrogen atmosphere, kept warm for 5 h, and cooled to room temperature to obtain a hard carbon material.

[0069] Example 8

[0070] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0071] (1) Crushing the lumpy weakly sticky coal into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0072] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt%;

[0073] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 3 g of petroleum asphalt and placed in a tubular furnace. The mixture was heated to 1300 °C at 5 °C / min under a nitrogen atmosphere, kept at this temperature for 5 h, and cooled to room temperature to obtain a carbonized sample.

[0074] (4) The carbonized sample obtained in step (3) was mixed evenly with o-carboxyphenylacetic acid in a mass ratio of 100:2 and placed in a tubular furnace. The mixture was heated to 200°C at a rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0075] Example 9

[0076] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0077] (1) Crushing the lump lignite into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0078] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt%;

[0079] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 3 g of coal tar pitch and placed in a tubular furnace. The mixture was heated to 1300° C. at 5° C. / min under a nitrogen atmosphere, kept at this temperature for 5 h, and cooled to room temperature to obtain a carbonized sample.

[0080] (4) The carbonized sample obtained in step (3) was mixed evenly with o-carboxyphenylacetic acid in a mass ratio of 100:2 and placed in a tubular furnace. The mixture was heated to 200°C at a rate of 5°C / min under an argon atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0081] Example 10

[0082] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0083] (1) Crushing the lump anthracite into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0084] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt%;

[0085] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 3 g of petroleum asphalt and placed in a tubular furnace. The mixture was heated to 1400° C. at 5° C. / min under a nitrogen atmosphere, kept at this temperature for 5 h, and cooled to room temperature to obtain a carbonized sample;

[0086] (4) The carbonized sample obtained in step (3) was mixed evenly with p-formylbenzoic acid in a mass ratio of 100:5 and placed in a tubular furnace. The mixture was heated to 200°C at a rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0087] Embodiment 11

[0088] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0089] (1) Crushing the lump anthracite into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0090] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt %;

[0091] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 6 g of petroleum asphalt and placed in a tubular furnace. The mixture was heated to 1500° C. at 5° C. / min under a nitrogen atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a carbonized sample.

[0092] (4) The carbonized sample obtained in step (3) was mixed evenly with salicylaldehyde in a mass ratio of 100:2 and placed in a tubular furnace. The mixture was heated to 300°C at a rate of 5°C / min under an argon atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0093] Example 12

[0094] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0095] (1) Crushing the lump lignite into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0096] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt %;

[0097] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 6 g of mesophase pitch and placed in a tubular furnace. The mixture was heated to 1300 °C at 5 °C / min under a nitrogen atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a carbonized sample.

[0098] (4) The carbonized sample obtained in step (3) was mixed evenly with salicylaldehyde in a mass ratio of 100:5 and placed in a tubular furnace. The mixture was heated to 200°C at a rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0099] Embodiment 13

[0100] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0101] (1) Crushing the lump anthracite into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0102] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt %;

[0103] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 3 g of petroleum asphalt and placed in a tubular furnace. The mixture was heated to 1300 °C at 5 °C / min under a nitrogen atmosphere, kept at this temperature for 5 h, and cooled to room temperature to obtain a carbonized sample.

[0104] (4) The carbonized sample obtained in step (3) was mixed with p-formylbenzoic acid in a mass ratio of 100:2 and placed in a tube furnace. The mixture was heated to 200°C at a rate of 5°C / min under an argon atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0105] Embodiment 14

[0106] This embodiment is a method for preparing a hard carbon material, which includes the following steps.

[0107] (1) Crushing the lump anthracite into coal powder, sieving the undersize material through a 325-mesh sieve, and controlling the particle size D50 of the coal powder to be 4 to 10 μm;

[0108] (2) taking 50 g of the coal powder obtained in step (1), adding it to 200 ml of an acid-washing deashing solution, washing it with water until the pH value is 6 to 8, and then drying it to obtain ultrapure coal powder with an ash content of ≤0.5 wt %;

[0109] (3) 30 g of the ultrapure coal powder obtained in step (2) was mixed evenly with 3 g of petroleum asphalt and placed in a tubular furnace. The mixture was heated to 1300 °C at 5 °C / min under a nitrogen atmosphere, kept at this temperature for 5 h, and cooled to room temperature to obtain a carbonized sample.

[0110] (4) The carbonized sample obtained in step (3) was mixed evenly with salicylaldehyde in a mass ratio of 100:2 and placed in a tubular furnace. The mixture was heated to 200°C at a rate of 5°C / min under an argon atmosphere, kept at this temperature for 2 h, and cooled to room temperature to obtain a hard carbon material.

[0111] Comparative Example 1

[0112] The difference between this embodiment and embodiment 1 is that step (3) is not mixed with at least one of petroleum asphalt, coal tar asphalt and mesophase asphalt. The remaining steps and parameters are the same as those in embodiment 1.

[0113] Comparative Example 2

[0114] The difference between this embodiment and embodiment 1 is that step (4) is not mixed with at least one of p-formylbenzoic acid, o-carboxybenzoic acid and salicylaldehyde. The remaining steps and parameters are the same as those in embodiment 1.

[0115] Comparative Example 3

[0116] The difference between this embodiment and embodiment 1 is that step (3) is not mixed with at least one of petroleum asphalt, coal tar asphalt, and mesophase asphalt, and step (4) is not mixed with at least one of p-formylbenzoic acid, o-carboxybenzoic acid, and salicylaldehyde. The remaining steps and parameters are the same as those in embodiment 1.

[0117] Comparative Example 4

[0118] The difference between this embodiment and embodiment 1 is that step (4) is mixed with o-toluic acid. The remaining steps and parameters are the same as those in embodiment 1.

[0119] Table 1 Performance test results of hard carbon materials obtained in Examples and Comparative Examples

[0120]

[0121]

[0122] By comparing the specific surface area data in Table 1, it can be seen that the specific surface area of ​​coal-based hard carbon materials is closely related to the initial charge and discharge efficiency. When the specific surface area is too high, such as in Example 1 and Comparative Example 3, the initial charge and discharge efficiencies are 88.78% and 79.81%, respectively. Too high a specific surface area will cause the electrolyte to react with the material surface to form SEI, consuming too much sodium ions, resulting in a decrease in the initial charge and discharge efficiency.

[0123] It can be seen from the data of Example 1 and Comparative Examples 1, 2, and 3 in Table 1 that the performance of Example 1, Comparative Example 1, and Comparative Example 2 are all improved relative to the blank control Comparative Example 3, among which Example 1 has the best effect. The reason is that petroleum asphalt is used as a soft carbon precursor for coating, and then an oxygen-containing functional group is introduced as a reversible adsorption site for sodium ions through an o-carboxyphenylacetic acid volume extracting agent, which is beneficial to the storage of sodium ions in the negative electrode material. It can be found from Example 1, Example 2, and Example 3 in Table 1 that as the coating amount of the petroleum asphalt soft carbon precursor increases, the capacity first increases and then decays, and the first charge and discharge efficiency shows a trend of increasing step by step. This is because petroleum asphalt has soft carbon characteristics under high-temperature carbonization and a high degree of graphitization, resulting in a decrease in capacity when the coating amount is too high. Comparing Example 1, Example 4, Example 5, Example 10, and Example 11 in Table 1, it can be found that the carbonization temperature has a certain effect on the battery capacity performance, showing a trend of first increasing and then decreasing. The reason is that when the carbonization temperature is too low, the hard carbon microcrystals are not fully developed, resulting in structural instability and poor battery performance; when the carbonization temperature is too high, the hard carbon microcrystals develop into long-range ordered graphite structures, with a high degree of graphitization and poor sodium storage capacity, resulting in poor performance. Comparing Example 1, Example 13, and Example 14 in Table 1, it can be found that different types of capacity-raising agents have a certain effect on the sodium storage capacity and the first charge and discharge efficiency. The reason is that the C=O functional group is more conducive to the reversible storage of sodium ions than -OH, so the capacity-raising effect of o-carboxyphenylacetic acid with more C=O and -OH functional groups is the most obvious, and p-formylbenzoic acid and salicylaldehyde are weakened in turn.

[0124] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a coal-based hard carbon material, characterized in that: The following steps are involved: (1) crushing, screening, acid washing and deashing the coal raw materials to obtain ultra-pure coal powder; (2) mixing the ultrapure coal powder obtained in step (1) with a soft carbon precursor and carbonizing the mixture under an inert atmosphere; (3) The carbonized sample obtained in step (2) is mixed with a volume extracting agent and subjected to secondary sintering and curing to obtain a coal-based hard carbon material.

2. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The extracting agent in step (3) is at least one of p-formylbenzoic acid, o-carboxyphenylacetic acid and salicylaldehyde; The mass ratio of the volume extracting agent to the carbonized sample in step (3) is (1-10):

100.

3. The method for preparing a coal-based hard carbon material according to claim 2, characterized in that: In step (3), the mass ratio of the volume extracting agent to the carbonized sample is (2-10):100 or (2-5):

100.

4. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The secondary sintering curing temperature in step (3) is 100-300° C., the heating rate is 1-10° C. / min, and the heat preservation time is 1-10 h.

5. The method for preparing a coal-based hard carbon material according to claim 4, characterized in that: The secondary sintering curing temperature is 100-300°C; the heating rate is 5-10°C / min; the heat preservation time is 2-10h; Alternatively, the secondary sintering curing temperature is 200° C., the heating rate is 5° C. / min, and the heat preservation time is 2 h.

6. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The coal raw material in step (1) is selected from at least one of anthracite, coking coal, fat coal, gas coal, weakly caking coal and lignite; The soft carbon precursor in step (2) is at least one of petroleum asphalt, coal tar pitch and asphalt mesophase; The mass ratio of the soft carbon precursor to the ultrapure coal powder in step (2) is (5-30):100; The carbonization temperature in step (2) is 1000-1600° C., the heating rate is 1-10° C. / min, and the insulation time is 1-10 h.

7. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: In step (2), the mass ratio of the soft carbon precursor to the ultrapure coal powder is (10-30):100 or 10:100; The carbonization temperature is 1000-1600°C; the heating rate is 5-10°C / min; the insulation time is 2-10h; Alternatively, the carbonization temperature is 1300-1400° C.; the heating rate is 5-10° C. / min; and the heat preservation time is 2-5 h.

8. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The coal raw material in step (1) is crushed and screened into coal powder with a particle size D50 of 4 to 10 μm; The acid washing and deashing in step (1) refers to adding the crushed coal powder into an acid washing and deashing solution, washing with water until the pH value is 6 to 8, and drying to obtain ultra-pure coal powder with an ash content of ≤0.5wt%; The inert atmosphere in step (2) refers to at least one of nitrogen, helium and argon; The secondary sintering and curing in step (3) is carried out under an inert atmosphere; the inert atmosphere refers to at least one of nitrogen, helium and argon.

9. A coal-based hard carbon material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the coal-based hard carbon material according to claim 9 in sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method of bituminous coal-based hard carbon material by combining pre-pore-forming and high-temperature carbonization

    CN118062827A

  • Performance improvement method of coal-based sodium ion battery negative electrode material and application thereof

    CN111293309A

  • Coal-based hard carbon negative electrode material of sodium ion battery, preparation method and application thereof

    CN113381013A

  • Surface modified hard carbon negative electrode material and preparation method and application thereof

    CN118160110A

Cited By

  • Coal-based hard carbon negative electrode material and preparation method and application thereof

    CN120004240A

  • Ash element regulated coal-based hard carbon material as well as preparation method and application thereof

    CN122380349A